2017
DOI: 10.3126/ijasbt.v5i3.18019
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of the Epizootic Ulcerative Syndrome in Pond Reared Carp Fish (Cyprinids) and It's Control Measure in Chitwan, Central Nepal

Abstract: A survey on epizootic ulcerative syndrome (EUS) was carried in carp fish (cyprinids) reared in ponds during January 2016 to January 2017 at six locations of Chitwan, Nepal. Outbreaks of EUS were observed in 39.6% of the carp during winter. EUS infection was the most for Cirrhinus mrigala (47.3% of the 170 samples) and the least for Labeo rohita (12.3% of the 65 samples). EUS infected fish weighing range between 15g-300g were characterized as extensive deep ulceration on head, dorsal and lateral part of body an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Rodgers et al, concluded the fact that translocation of live aquatic species posed a greater risk of spread of infection than moving dead goods (Rayamajhi et al, 2017). The potential of pathogen transmission, disease invasion, and subsequent outbreaks of disease in the current aquaculture systems increases with the introduction of new exotic fish species to aquaculture (Faruk et al, 2004).…”
Section: An Account Of Major Fish Diseasesmentioning
confidence: 99%
“…Rodgers et al, concluded the fact that translocation of live aquatic species posed a greater risk of spread of infection than moving dead goods (Rayamajhi et al, 2017). The potential of pathogen transmission, disease invasion, and subsequent outbreaks of disease in the current aquaculture systems increases with the introduction of new exotic fish species to aquaculture (Faruk et al, 2004).…”
Section: An Account Of Major Fish Diseasesmentioning
confidence: 99%